Communication audit of Doto Coffee's promotion strategy for the Bicycle community - Septian Alin Fithar, Lalu; Routania Fransiska, Olva (Universitas Ahmad Dahlan, 2024)
The coffee shop business is increasingly mushrooming in Lombok, and this causes coffee shops to carry out many promotional strategies to compete with competitors and bring in many customers. Coffee shops carry out many kinds of promotions through social media by targeting a diverse target audience. The promotions carried out by coffee shops target the community for cooperation. Approaching the community is a challenge for coffee shops. This study aims to conduct a communication audit on the discount promotion program for Doto coffee bicycle users. The method used in this research is a descriptive qualitative method with a communication audit approach using the SOSTAC model. SOSTAC approach has six stages: Situation analysis, Objective, Strategy, Tactics, Actions, and Control. The results of the communication audit state that the promotional strategy carried out by Doto Coffee has used promotional principles, although many things could be improved. Overall problem. The problem is more dominant in the need for more variation in Doto Coffee's promotional strategies to bring in the bicycle community. The strategy used is only on social media but does not use the community relations approach, even though Doto Coffee's goal is to bring in the community. The recommendations given from this research to Doto Coffee are expected to approach using community relations and social media as a promotional medium to bring in the community and increase community trust.